CORRELATION OF HUMAN MOVEMENT SYSTEM MATERIAL IN SALAT MOVEMENT: STUDY OF INTEGRATION OF SCIENCE AND RELIGION - Muhammad Nasrudin (Science Education, Institut Agama Islam Negeri Ponorogo, 2022)
Learning science of the human movement system material level that must be achieved by students is knowledge, understanding, and application. Based on interviews conducted, to reach that level at Madrasah Tsanawiyah Negeri Lumajang using an integration method between the material of the human movement system and salat movements, even though it is only macro. The focus of the problem is: 1) the relationship between the material system of motion in humans and the movement of salat. 2) the impact of the material relationship of the motion system on the human movement of salat. The type of research used is descriptive qualitative with data analysis techniques using the Miles and Huberman method. The results of the study show that there is a relationship between the material of the motion system in humans and the movement of salat. Among them when takbiratul ihram is related to the upper arm movement system. Meanwhile, the impact of the material relationship between the human movement system and salat movements: 1) keep the muscles from being stiff, prevent bone disease and maximize the work of existing joints. 2) bring up religious character for students at MTsN 1 Lumajang.